Pelaksanaan Evaluasi Pembelajaran Pendidikan Jasmani Olahraga dan Kesehatan oleh Guru SMA Negeri Se-Kecamatan Sukorejo Kabupaten Kendal - Ariyanto, Okka Indah; Yuwono, Cahyo (Universitas Negeri Semarang, 2023)
Focus on this research to find out the circumstances and problems of learning evaluation in the post-Covid-19 pandemic period, both in terms of learning planning, learning implementation, and learning evaluation. The method used by researchers is a descriptive method with a qualitative approach. Data collection techniques are carried out with direct interviews, observations, and documentation Learning planning, learning implementation, and learning evaluation have not gone well. In learning planning there are components that are not listed in the rpp and the use of media, in the implementation of learning. The learning activities carried out are also not in accordance with the rpp that has been made. The final process of learning is also absent. Evaluation of learning during a pandemic does not go well because teachers only rely on affective and cognitive assessments, but psychomotor cannot be implemented. Suggestions for PJOK teachers to be able to develop a more complete lesson plan, so that the learning process can be carried out properly and learning objectives can be achieved and for schools to supervise teachers so that they can work more optimally and fulfill the facilities needed for the learning process.